Legal Aid and Pro Bono Reveal Differences in the Implementation of Indonesian Law - Elmiati Nurdin; Nur Ilmi Putri Febriyanti; Nur Annisa Putri; Evi Selviani; Erni Yoesry (IJBLE Scientific Publications Community Inc., 2026)
This study aims to examine the fundamental differences between legal aid and pro bono in the Indonesian legal system and identify challenges that hinder their effective implementation. Using normative legal research methods with a statutory and comparative approach, data are analyzed from various legal documents, scientific literature, and relevant regulations. The results show that legal aid, which is funded by the state and strictly regulated, differs fundamentally from pro bono, which is voluntary and funded by lawyers or law firms. These differences include funding sources, regulatory basis, and service scope. This study also uncovers challenges such as unequal distribution of services, limited resources, and role ambiguity among legal aid providers. The novelty of this study lies in emphasizing the urgency of establishing clear regulations and systematic role allocation to expand access to justice, particularly for vulnerable groups. These findings are recommended as a basis for consideration in legal aid policy reform in Indonesia.